If The Snake : Pierre Huyghe. - Huyghe, Pierre; Stenne, Anne (Köln : Verlag der Buchhandlung Walther und Franz König, 2024)
Atoui, Tarek ; Barney, Matthew ; Chan, Paul ; Cheng, Ian ; Dubbin, Melissa ; Davidson, Aaron S. ; Gerrard, John ; Giraud, Fabien ; Siboni, Raphaël ; Bead, Glass ; Hénaff, Elizabeth ; Huyghe, Pierre ; L'Hoest, Eva ; Ortega, Fernando ; Raspet, Sean ; Reynaud-Dewar, Lili ; Rosenkranz, Pamela ; Sehgal, Tino ; Tajima, Mika
Okayama Art Summit 2019
boek